Establishing the Optimal Viral Load Threshold for Initiation of Therapy for Cytomegalovirus Infection in Hematopoietic Stem Cell Transplant Recipients: A Prospective Derivation Cohort Study Using the International Standardized CMV Quantitative Nucleic Acid Testing. (4th October 2017) - Hanna, Zachary; Karrick, Megan; Jayaprakash, Rachna; Morgan, William; Lutfi, Samaa; Gunasekaran, Kulothungan; Busto, Ramon Del; Alangaden, George; Abreu-Lanfranco, Odaliz; Samuel, Linoj; Ramesh, Mayur
Abstract: Background: Cytomegalovirus infection remains a critical concern following hematopoietic stem cell transplantation (HSCT). Despite the international standardization in CMV viral load (VL) monitoring, establishment of a threshold viral load to guide preemptive management has yet to be determined. Our primary goal is to obtain a threshold CMV VL for the early detection of clinically significant viremia and, subsequently, for guiding initiation of early management. Secondary goals are to provide clarification to diagnosing clinically significant CMV viremia and to develop an algorithm to ease clinical decision-making. Methods: A prospective cohort analysis of CMV viral loads using the COBAS ® AmpliPrep/COBAS ® TaqMan ® CMV Test (CAP/CTM) was conducted in all HSCT recipients undergoing weekly CMV monitoring at Henry Ford Hospital, Detroit, MI from April 2015 to December 2016. Plasma CMV quantitative PCR analysis was performed using the CAP/CTM assay. CMV VL were then calibrated to the WHO international standard and reported in international units (IU/mL of plasma). Each event of early CMV viremia was then categorized as clinically significant or non-clinically significant. An ROC curve analysis was then utilized to identify the optimal CMV VL threshold value for predicting clinically significant CMV viremia. Results: Sixty-three allogeneic HSCT recipients were included in the study with a total of 240 (viremic and non-viremic) events observed. Twenty-two patients experienced a total of 27 CMV viremic events. Twenty-six of 27 CMV events were clinically significant. Using an ROC curve, a viral load of 329 IU/mL of plasma was determined as the optimal threshold value for predicting clinically significant CMV viremia (sensitivity 100%, specificity 99.5%, NPV 100%, PPV 96.3%). Conclusion: Our study offers a novel approach to classifying and detecting early clinically significant CMV viremia and a preliminary threshold CMV VL value at which preemptive therapy should be considered. A prospective validation cohort is currently in progress. Disclosures: All authors: No reported disclosures.